Pressure Injury Education in the Department of Veterans Affairs: Results of a National Wound Provider Cross-sectional Survey. Issue 5 (September 2018) - Cowan, Linda; Garvan, Cynthia; Rugs, Deborah; Barks, Lelia; Chavez, Margeaux; Orozco, Tatiana
Abstract : PURPOSE: The aim of this study was to describe experience, training, educational needs and preferences, and perceptions of pressure injury (PI) prevention education of wound care providers in the Veterans Health Administration (VHA) of the Department of Veterans Affairs (VA) as an indicator of effectiveness of the mandated VHA PI Prevention Program. SUBJECTS AND SETTING: A convenience sample of national VHA wound care providers practicing in VHA facilities was compiled from members of special interest groups and committees and by referrals from known wound care specialists and clinicians (N = 1726). The response rate was 24% (n = 410). DESIGN: Cross-sectional, descriptive study. METHODS: A 42-item online cross-sectional survey was administered via a blast-email of the survey link to the sample. The survey link was active for 1 month (March 3-31, 2014). The survey queried demographic data, PI experience and education, and their perceptions and preferences for PI education. Quantitative responses underwent descriptive analyses, and responses to open-ended questions were analyzed by content analysis. RESULTS: The majority of the 415 respondents completed most of the questionnaire (n = 310, 74%). Half were board-certified providers with a mean wound care experience of 14.2 years (standard deviation = 9.8 years). Preference for type of wound training ranged from 17% for online gaming to 82% for face-to-face training. Training provided by facilities was perceived to be inadequate for wound care by 60% (n = 175) and inadequate for PI care by 49% (n = 142). CONCLUSIONS: The 2 greatest areas of need in PI care identified by wound care providers were education and documentation. These same issues were identified as problematic by an audit of PI prevention and management at 47 VHA facilities that was conducted by the VA Office of Inspector General. Abstract : Supplemental Digital Content is Available in the Text.